2021
DOI: 10.1021/acsabm.1c00362
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of Electrode Surface for Enhanced Bacterial Adhesion and Reactions: A Review on Recent Approaches

Abstract: The study of bacterial adhesion and its consequences has great significance in different fields such as marine science, renewable energy sectors, soil and plant ecology, food industry, and the biomedical field. Generally, the adverse effects of microbial surface interactions have attained wide visibility. However, herein, we present distinct approaches to highlight the beneficial aspects of microbial surface interactions for various applications rather than deal with the conventional negative aspects or preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 290 publications
0
12
0
Order By: Relevance
“…Microbial fuel cells (MFCs) are ecofriendly bioenergy harvesting and wastewater treatment technologies. The anode in MFCs provides bacterial colonization sites for biofilm attachment and electron transfer paths to receive the metabolized electrons . The crystal structures of outer membrane c-type cytochromes (OMCs) and pili analyzed by cryo-TEM unveiled that the electron transmembrane and extracellular electron-transfer (EET) processes are mainly determined by the interface between OMCs or flavin–OMCs complex and anode. It is challenging to obtain high MFCs power density without the formation of active biofilm with enriched exoelectrogens and the fast electronic/ionic transfer rates. , Thus, the question of how to strengthen the microorganism–anode interface to simultaneously favor the bacterial attachment and promote EET process is a great challenge. …”
Section: Introductionmentioning
confidence: 99%
“…Microbial fuel cells (MFCs) are ecofriendly bioenergy harvesting and wastewater treatment technologies. The anode in MFCs provides bacterial colonization sites for biofilm attachment and electron transfer paths to receive the metabolized electrons . The crystal structures of outer membrane c-type cytochromes (OMCs) and pili analyzed by cryo-TEM unveiled that the electron transmembrane and extracellular electron-transfer (EET) processes are mainly determined by the interface between OMCs or flavin–OMCs complex and anode. It is challenging to obtain high MFCs power density without the formation of active biofilm with enriched exoelectrogens and the fast electronic/ionic transfer rates. , Thus, the question of how to strengthen the microorganism–anode interface to simultaneously favor the bacterial attachment and promote EET process is a great challenge. …”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, such living electrodes are obtained by natural biofilm formation, [171,175,176] increasing the surface-area-to-volume ratio of the electrode, [20,[177][178][179][180] or modifying the electrode surface free energy to favor bacterial attachment. [174,181] More recently, the conductive polymer poly(3,4-ethylenedioxythiophene) (PEDOT) gained considerable attention in the field of bioelectronics because of its biocompatibility, good electric and ionic conductivity, and chemical stability. [182] Encouraging results were reported from conductive tissue scaffolding, [183] neural probing, [184] and electroactive living materials.…”
Section: Living Electrodesmentioning
confidence: 99%
“…However, it is reported that the edge of the layer of graphite flakes possibly induces oxidative stress on bacteria or penetrates the bacterial membrane and thereby inhibits bacterial adhesion . Several surface modification approaches, including chemical, electrochemical, mechanical, thermal, and pressure treatments, have been carried out to enhance the surface properties and to increase the bacterial EET . Nanomaterial-based surface modification is the simplest and most widely used technique. , However, these methods are not economically feasible to be employed for practical applications in BESs.…”
Section: Introductionmentioning
confidence: 99%
“…19 Several surface modification approaches, including chemical, electrochemical, mechanical, thermal, and pressure treatments, have been carried out to enhance the surface properties and to increase the bacterial EET. 20 Nanomaterial-based surface modification is the simplest and most widely used technique. 21,22 However, these methods are not economically feasible to be employed for practical applications in BESs.…”
Section: Introductionmentioning
confidence: 99%